Ethical life in South Asia/ edited by Anand Pandian and Daud Ali - "Pandian, Anand (ed.);Ali, Daud (ed.)" (New Delhi, 2011)
Breaking from prevailing conceptions of ethics and morality as matters of moral rule or principle, this volume calls attention to ethical life in South Asia-the moral dispositions at work in lived experience, and the embodied practices of ethical engagement through which such dispositions may be cultivated and shared. Using approaches from history, anthropology, religious studies, and philosophy, these original essays constitute an unprecedented regional and interdisciplinary engagement with the essential question of how one ought to live. Taking up themes such as the transmission of tradition, ethical engagements with modernity, ethical practices of the self, and moral relations between self and others, this volume puts South Asian traditions of ethical life into conversation with the Aristotelian, Christian, and liberal traditions that have been so consequential for ethical life in the West.
Keywords: Religion and ethics